Bluetooth Remote Home Automation System Using Android Application - Ramlee, Ridza Azri; LEONG , MAN HONG; SARBAN SINGH , RANJIT SINGH A/L; ISMAIL, MOHD MUZAFAR; OTHMAN , MOHD AZLISHAH; SULAIMAN , HAMZAH ASYRANI; MISRAN , MOHAMAD HARRIS; MEOR SAID , MAIZATUL ALICE (2013)
This paper presents the overall design of Home Automation System (HAS) with low cost and wireless remote control. This system is designed to assist and provide support in order to fulfill the needs of elderly and disabled in home. Also, the smart home concept in the system improves the standard living at home. The main control system implements wireless Bluetooth technology to provide remote access from PC/laptop or smart phone. The design remains the existing electrical switches and provides more safety control on the switches with low voltage activating method. The switches status is synchronized in all the control system whereby every user interface indicates the real time existing switches status. The system intended to control electrical appliances and devices in house with relatively low cost design, user-friendly interface and ease of installation.